Pendidikan Akhlak dalam QS. Lukman - Asmullah (Inspiratif Pendidikan, 2025)
The purpose of this study is to elaborate on moral education contained in QS. Lukman/31: 13-19, the goal is to form noble morals for all individuals, especially for those seeking knowledge and the next generation. The focus of the research in this paper is: 1) How is Moral Education contained in QS. Lukman. 2). What are the benefits of moral education contained in QS. Lukman and its implementation in life. To answer this research, a qualitative approach and descriptive analysis method are used using the type of library research by collecting primary and secondary data including verses of the Qur'an and the opinions of experts in interpretation related to moral education in various books and writings in order to obtain a deep and accurate understanding. The results of this study indicate that moral education contained in QS. Lukman/31: 13-19 includes monotheism education, respecting both parents, being motivated to do good, carrying out orders, being humble, and being modest. The benefits of moral education contained in QS. Lukman and its implementation in life are to elevate human status to a noble status. Because by implementing moral education contained in QS. Lukman/31; 13-19, humans always improve their relationship with the Creator, namely Allah SWT, improve their relationship with other humans, improve their morals towards themselves, and improve their morals towards the environment.